Current HIV/AIDS end-of-life care in sub-Saharan Africa: a survey of models, services, challenges and priorities - O'Neill Joseph F; Marconi Katherine; Stewart Karen; Harding Richard; Higginson Irene J (BMC, 2003)
Abstract Background In response to increased global public health funding initiatives to HIV/AIDS care in Africa, this study aimed to describe practice models, strategies and challenges to delivering end-of-life care in sub-Saharan Africa. Methods A survey end-of-life care programs was conducted, addressing the domains of service aims and configuration, barriers to pain control, governmental endorsement and strategies, funding, monitoring and evaluation, and research. Both closed and qualitative responses were sought. Results Despite great structural challenges, data from 48 programs in 14 countries with a mean annual funding of US $374,884 demonstrated integrated care delivery across diverse settings. Care was commonly integrated with all advanced disease care (67%) and disease stages (65% offering care from diagnosis). The majority (98%) provided home-based care for a mean of 301 patients. Ninety-four percent reported challenges in pain control (including availability, lack of trained providers, stigma and legal restrictions), and 77% addressed the effects of poverty on disease progression and management. Although 85% of programs reported Government endorsement, end-of-life and palliative care National strategies were largely absent. Conclusions The interdependent tasks of expanding pain control, balancing quality and coverage of care, providing technical assistance in monitoring and evaluation, collaborating between donor agencies and governments, and educating policy makers and program directors of end-of-life care are all necessary if resources are to reach their goals.